Government Ideology and Tuition Fee Policy: Evidence from the German States - Björn Kauder; Niklas Potrafke (Center for Economic Studies and ifo Institute (CESifo), 2013)
In January 2005 the German Supreme Court permitted the state governments to charge tuition fees. By exploiting the natural experiment, we examine how government ideology influenced the introduction of tuition fees. The results show that rightwing governments were active in introducing tuition fees. By contrast, leftwing governments strictly denied tuition fees. This pattern shows clear political alternatives in education policy across the German states: the political left classifies tuition fees as socially unjust; the political right believes that tuition fees are incentive compatible. By the end of 2014, however, there will be no tuition fees anymore: the political left won four state elections and abolished tuition fees. In Bavaria the rightwing government also decided to abolish tuition fees because it feared to become elected out of office by adhering to tuition fees. Electoral motives thus explain convergence in tuition fee policy.
Keywords: D72; I22; I28; H75; 330; tuition fees; education policy; government ideology; partisan politics